Determination of the total neutron cross section for natural hafnium on the filtered neutron beam with 2 keV energy - О. О. Gritzay; А. K. Grymalo; V. A. Pshenychnyi (Ядерна фізика та енергетика)
Unshielded value of the total neutron cross section of the natHf at the neutron 2 keV energy was obtained. The MCNP 4С code and measurement results obtained with using six samples for thicknesses from 0.00236 to 0.01257 nucl/b were used for determination of the unshielded value of the natHf cross section. Obtained value of the total neutron cross section of the natHf was compared with the data of other authors and with data from the evaluated nuclear data libraries.